Trademarks and the patent premium value: Evidence from medical and cosmetic products. (June 2015) - Thoma, Grid
Abstract: The determinants of the premium value of patents for medical and cosmetic products are analyzed with respect to a complementary IP strategy such as trademarks. I discuss a novel method and database to gauge combinations of patent and trademark pairs regarding the same innovative project. The premium value is computed through a model of renewal decisions for the patent cohorts 1985–1990 that have been designated in the U.K. and Germany. After taking into the account several firm characteristics and patent indicators typically used in the literature, I find ample evidences that patent and trademark pairs are featured by higher valuations. Highlights: Patent and trademark pairs are combined IP strategies that concern the same innovative project. A novel method and database is proposed in order to gauge a patent and trademark pair. Combined IP strategies function as a signaling device and expand patent protection. Patent and trademark pairs enhance the premium value of patents.